CONSTRUCTION OF RECOMBINANT PLASMID FROM EXPRESSION VECTOR PAC7 CONTAINING ENTP GENE FUSED WITH FRAGMENTS OF BAAMYF1 AND BAAMYF2 FOR PRODUCTION OF ENTEROCIN P IN BACILLUS SUBTILIS 168 - Nhàn, Nguyễn Thanh; Minh Đức, Phạm Thị; Ngọc, Lê Thu; Trường, Lê Văn; Huyền, Đỗ Thị; Tân, Trần Ngọc; Linh, Phạm Thùy; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2013)
With high antimicrobial activity against a broad range of spoilage and food-borne gram positive pathogenic bacteria such as Listeria monocytogenes, Staphylococcus aureus, enterocin P, a class IIa bacteriocin produced by Enterococcus faecium P13, has been studied in expression in different heterologous systems recently. In this work, enterocin P was expressed in host cells of B. subtilis 168. Enterocin P was produced in the chimeric form with fragments of amylase from B. amyloliquefaciens (BaamylF1, BaamylF2) in order to avoid degrative activity of host proteases. The fusion genes of entP and baamylF1 or baamylF2 were ligated to pAC7, resulting in recombinant plasmids pAC-amyF1-entP and pAC-amyF2-entP. These linearized plasmids were transformed to the competent cells B. subtilis 168 and integrated into the host genome. The chimeric proteins, BaamylF1-Enterocin P and BaamylF2-Enterocin P heterologously secreted from the recombinant B. subtilis strains were concentrated with 50% (NH4)2SO4 and then treated with 50% formic acid to cleave enterocin P from the fusion forms. As a result from antimicrobial activity test, recombinant Enterocin P obtained after cleavage of fusion proteins showed an inhibitory effect on growth of indicator microorganisms, S. aureus and B. cereus, food-borne gram positive pathogenic bacteria. Thus, enterocin P was produced heterologously with biological activity, despite low expression level.